KESADARAN HUKUM MASYARAKAT PADA TINDAK PIDANA POLITIK UANG DALAM PENYELENGGARAAN PEMILU DAN PILKADA TAHUN 2024 DI KARAWANG - Abas, Muhamad; Hidayat, Anwar; Nopianti, Wike; Al Naupal, Raden Hisyam (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2025)
Democracy in the government system is very dependent on the General Election (Pemilu) mechanism which upholds the principles of transparency and equality, where elections are an important instrument to accommodate people's aspirations and ensure the change of power in a dignified manner. However, the dirty practice that often surrounds the democratic process is the phenomenon of Money Politics or Transactional Politics, which can be defined as a systematic effort to influence voter preferences through material compensation, whether in the form of cash, goods or promises of economic value. This practice can significantly weaken the true essence of democracy, namely popular sovereignty. The Indonesian government has anticipated this problem through comprehensive legal instruments, namely regulations related to Money Politics which are contained in a number of laws, especially Law no. 7 of 2017 concerning Elections and Law no. 10 of 2016. Specifically, Article 523 regulates forms of Money Politics violations in three critical phases: the campaign period, the quiet period, and during voting, with legal consequences that have been explicitly formulated in the regulation, aimed at preventing practices that can distort democratic process and undermine the integrity of general elections